Methodological and pedagogical conditions of organization of independent work of students in classes miniature painting - E.V. Shachkova (Academy of Cognitive and Natural Sciences, 2009)
In article the problem of the organisation of metodiko-pedagogical conditions of independent work on discipline is considered: "Tiny painting and a drawing".